Financial system development and economic growth in selected African countries: evidence from a panel cointegration analysis - Starkey, Randall Ashley (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2011)
Financial systems (i.e. banking systems and stock markets) can influence economic growth by performing the five key financial functions, namely: mobilising savings, allocating capital, easing of exchange, monitoring and exerting corporate governance, as well as ameliorating risk. The level of development of the financial system is a key determinant of how effectively and efficiently these functions are performed. This study examines the short-run and long-run relationships between financial system development and economic growth for a panel of seven African countries (namely: Egypt, Ivory Coast, Kenya, Morocco, Nigeria, South Africa and Tunisia) covering the period 1988 to 2008. While numerous empirical studies have researched this topic, none of the previous African empirical literature have investigated thjs by using three groups of financial development measures (i.e. overall financial development, banking system development and stock market development measures) as well as employing panel cointegration analyses. The investigation of the long-run finance-growth relationship is conducted using two methods; the Pedroni panel cointegration approach and the Kao panel cointegration technique. The Pedroni panel cointegracion approach is more often applied in empirical research as it has less restrictive deterministic trend assumptions, while the Kao panel cointegration technique is employed in this study for comparison purposes. Furthermore, the short-run linkages betveen financial development and economic growth are analysed using the Holtz-Eakin d of (1989) panel Granger causality test. The results of the Pedroni cointegration tests show that there are long-run relationships between overall financial development (measured by LOFD and OFD2) and economic growth, banking system development (measured by LPSC) and economic growth, as well as stock marker development (measured by LMCP and LVLT) and economic growth. In contrast, the Kao test fails to find any cointegration between finance and growth. However, on the balance, findings largely support a conclusion of cointegration between financial development and economic growth since the Pedroni approach is more appropriate for examining cointegration in heterogeneous panels. Estimates of these long-run cointegrating relationships show that all five financial development measures have the expected positive linkages with growth. However, only four of the five financial development measures were found to have significant long-run linkages with growth, as the relationship between LOFD and growth was not found to be significant in the long-run. The panel Granger causality results show that economic growth Granger causes banking system development in the short-run (i.e. there is demand-following finance), irrespective of the measure of banking development used. While there is bi-directional, reciprocal causality between economic growth and both of the measures of overall financial development and one measure of srock market development (i.e. LVLT). Thus, pulicy makers should focus on formulating policy which promotes faster paced economic growth so as to stimulate financial development, while at the same time encourage policy that promotes the balanced expansion of the banking systems and srock markets in ordet to augment economic growth.
Keywords: Economic development -- Africa; Economic development -- Developing countries; Banks and banking -- Africa; Banks and banking -- Developing countries; Stock exchanges -- Africa; Stock exchanges -- Developing countries; Econometric models; Economic policy -- Africa; Economic policy -- Developing countries